Success rate of paper patch myringoplasty in patients with tympanic membrane perforation: A retrospective analytics study of 110 cases - Sanathorn Chowsilpa (2018)
© 2018, Medical Association of Thailand. All rights reserved. Background: Paper patch myringoplasty is a simple procedure to close perforated tympanic membranes, however, the success rate varies between 12.5% and 84.2%. Objective: To evaluate the success rate of paper patch myringoplasty and identify the factors relating to the successful patching. Materials and Methods: A retrospective medical chart review of 110 patients that underwent paper patch myringoplasty was done. The factors affecting successful paper patching, including etiologies of the tympanic membrane perforation, location of the perforation, last infection, perforation size, characters of perforation edge, and middle ear mucosa, were statistically analyzed. Results: The success rate of paper patch myringoplasty was 27.27%. Factors affecting successful paper patching were statistically analyzed and showed no significant difference. However, the success rate tended to be higher in patients with perforation less than 5% of total area (p-value 0.431), posteroinferior perforation (p-value 0.086), and traumatic perforation (p-value 0.153). The patients with successful closure significantly improved hearing in average air conduction (p-value <0.001), average bone conduction (p-value 0.014), and air bone gap (p-value 0.006). Conclusion: Although the present study showed low success rate of paper patch myringoplasty, this procedure may be beneficial in selected patients, including patients with small perforation, posteroinferior perforation, or traumatic perforation.